2022
DOI: 10.1108/whatt-05-2022-0058
|View full text |Cite
|
Sign up to set email alerts
|

What innovations would enable the tourism and hospitality industry in Africa to re-build?

Abstract: PurposeThis paper discusses the outcomes of an exploratory study into the innovations, adaptations, and best practices that the tourism and hospitality sector in Africa should implement in dealing with coronavirus disease 2019 (COVID-19) pandemic-induced disruptions.Design/methodology/approachThis paper was based on data collected through qualitative approaches by reviewing published academic articles and unpublished documents, including websites, media reports and global public health entities such as the Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The development of hotel applications (hotel apps) for resident guests in hotels gained popularity as guest could get all the hotel info on the up instead of the traditional hotel directory placed in the rooms. These results on new technological innovations in the hotel industry are in line with studies conducted by Bama, Nyathela & Makuzva, 2022. The respondents also reported that they noted increased operational efficiency and productivity rate per employee and fewer employees on sick offs.…”
Section: New Technological Process Innovationssupporting
confidence: 85%
See 1 more Smart Citation
“…The development of hotel applications (hotel apps) for resident guests in hotels gained popularity as guest could get all the hotel info on the up instead of the traditional hotel directory placed in the rooms. These results on new technological innovations in the hotel industry are in line with studies conducted by Bama, Nyathela & Makuzva, 2022. The respondents also reported that they noted increased operational efficiency and productivity rate per employee and fewer employees on sick offs.…”
Section: New Technological Process Innovationssupporting
confidence: 85%
“…The pandemic has proved to be the catalyst for innovation and integration of new technologies for the travel and tourism sector. It has opened new prospects for the development of information and communication technologies (Bama, Nyathela & Makuzva, 2022). Their study found that digitization, collaborations, partnerships and integrated governance frameworks as key adaptations and best practices for the hospitality sector in Africa.…”
Section: New Opportunities Identified By 4-and 5-star Hotels In Kenya...mentioning
confidence: 99%
“…Overwhelming trends suggest the domestic tourism market does not have the spending capacity of international visitors. The fragmented, cascaded and sometimes disorganised approach in dealing with policy adoptions and implementation in managing developments around the pandemic further inhibits a compelling approach to continent-wide tourism and hospitality revival (Bama et al. , 2022).…”
Section: Africamentioning
confidence: 99%
“…This led to a decline in consumer spending, job losses, and product demand [5]. To develop sustainable economies, firms embraced new technologies and investments in healthcare, biotechnology, and renewable energy [6]. It is crucial for the industrial sector to innovate and adapt as the world recovers from the epidemic.…”
Section: Introductionmentioning
confidence: 99%